Physical deterioration of soil and rice productivity in rural Java. Issue 1 (February 2021) - Irawan, S; Antriyandarti, E
Abstract: Soil degradation is one of the world's most serious ecological and environmental problems affected agricultural productions. The agricultural sector defines land degradation as a process of decreasing land productivity that is temporary or permanent, characterized by a decrease in physical, chemical, and biological properties. This study aims to investigate the impact physical deterioration of which occurs in the form of structure fertilizer application on rice productivity. This study applied Autoregressive model to analyse the primary data collected from 4 main rice producer areas in Central Java and East Java, namely Cilacap, Grobogan, Lamongan and Jember. The results show that previous chemical fertilizer use has negative impacts on rice productivity. Inorganic chemical fertilizers have an important role in increasing productivity, but at the same time the uncontrolled use of it is one of the causes of the decline in the quality of biological, physical, and chemical fertility of the soil.